The Role of Social Services in Overcoming Beggars in Medan City - Sri Sudiarti; Rika Putri Harapan (Penerbit Jurnal Indonesia, 2022)
The purpose of this study is to identify the efforts made by the social services agency in dealing with the increasing number of beggars in Medan, as well as the challenges faced in the process. Descriptive qualitative research method is used in this study. Researchers are looking for more information about the steps, problems, and assistance faced by the social service in an effort to curb beggars in the city of Medan. Participant observation, interviews, and documentation were used to collect data. Data reduction, presentation, and drawing conclusions are part of the data analysis stage. The findings indicate that the social service of the city of Medan has fulfilled the responsibilities of collecting data, monitoring, and fostering beggars. However, there are still some obstacles in its implementation, including the lack of cooperation and the law that prohibits beggars..